Refurbishment Manual : Maintenance, Conversions, Extensions - Fisch, Rainer; Krause, Harald; Lenz, Bernhard; Musso, Florian; Rudolphi, Alexander (Birkhäuser, 2012)
A practical planning aid for conversions and extensions to existing structures, this manual offers concrete tips on planning steps and cost analysis, covers all aspects from energy-efficiency to fire protection and historic preservation, with clear constructional solutions and built projects as examples.